28.4k views
3 votes
Please help but only answer if you're going to show work please!!!!

Please help but only answer if you're going to show work please!!!!-example-1
User Ar
by
5.4k points

2 Answers

5 votes
input h = - 2 into the expression

4[3(-2) - 6]
---------------
1 + (-2)

4[-6 - 6]
= ---------------
-1

4[-12]
= ---------------
-1

-48
= ----------
-1
= 48
User Alex Aza
by
6.2k points
1 vote
To solve this problem you must apply the proccedure shown below:

1. You have the following expression given in the problem above:

4(3h-6)/(1+h)

2. Then, if h is h=-2, you have to substitute this value into the expression given above, as below:

4(3h-6)/(1+h)
4(3(-2)-6)/(1+(-2))

3. Then, you have
4(-6-6)/(1-2)
4(-12)/-1
-48/-1
48
User Radek Lopatecki
by
5.2k points